129k views
2 votes
Solve for b. a = 9b2c

Solve for b. a = 9b2c-example-1

2 Answers

3 votes

Answer:

b=+-sqrt(ac)/3c (4th)

Explanation:

a = 9b^2c

b^2=a/9c

b=+-sqrt(a)/3(sqrt(c))

b=+-sqrt(ac)/3c

User Sam Sha
by
5.5k points
3 votes

The solution for b is b=±√ac/9. Option a is the correct choice.

We begin by dividing both sides of the equation by 9b²c to isolate b:

a / (9b²c) = 1

Simplifying the left side, we get:

a/9b² = 1/c

Taking the square root of both sides, we obtain:

√(a/9b²) = √(1/c)

Simplifying the left side and solving for b, we find:

√(ac)/9b = 1/c

b = ±√ac/9

Therefore, the solutions to the equation a=9b²c are:

b = ±√ac/9

Note that both positive and negative values of b satisfy the equation.
Option a is the correct choice.

User BlamKiwi
by
5.8k points